2022
DOI: 10.1126/sciimmunol.abk2092
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Gasdermin D shapes the host-microbial interface by driving mucus layer formation

Abstract: Goblet cells and their main secretory product, mucus, play crucial roles in orchestrating the colonic host-microbe interactions that help maintain gut homeostasis. However, the precise intracellular machinery underlying this goblet cell–induced mucus secretion remains poorly understood. Gasdermin D (GSDMD) is a recently identified pore-forming effector protein that causes pyroptosis, a lytic proinflammatory type of cell death occurring during various pathophysiological conditions. Here, we reveal an unexpected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 63 publications
3
52
1
Order By: Relevance
“…In addition, Rana et al identified methotrexate as a non-inflammatory stimulus capable of upregulating GSDMB, and Zhang et al successfully established an in vitro colon organoid culture system by three-dimensional printing. 1 , 2 These findings provide strong support for the further development of drugs targeting GSDMs and optimization of therapeutic strategies for the treatment of IBD. It is worth noting that more and more studies have been conducted on the pyroptosis-independent functions of GSDMs.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…In addition, Rana et al identified methotrexate as a non-inflammatory stimulus capable of upregulating GSDMB, and Zhang et al successfully established an in vitro colon organoid culture system by three-dimensional printing. 1 , 2 These findings provide strong support for the further development of drugs targeting GSDMs and optimization of therapeutic strategies for the treatment of IBD. It is worth noting that more and more studies have been conducted on the pyroptosis-independent functions of GSDMs.…”
mentioning
confidence: 74%
“…Recently, Rana et al and Zhang et al published two studies illustrating the important regulatory roles of gasdermin B (GSDMB) and -D (GSDMD) in inflammatory bowel disease (IBD) and intestinal immune homeostasis maintenance, respectively. 1 , 2 Their findings collectively indicate that the gasdermins (GSDMs) can play a crucial role in restoring epithelial barrier function and shaping gut mucosal homeostasis. Moreover, neither of the functions of GSDMs revealed by these two studies are related to pyroptosis, which may provide new insights into the non-pyroptosis-dependent functions of GSDM proteins.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The release of granule stored neutrophil elastase into the cytosol can also act on GSDMD to generate a N-terminal pore-forming fragment which, in this case, was associated with neutrophil death and, therefore, the loss of GSDMD increased neutrophil levels and the hosts ability to combat extracellular E. coli infection [ 13 ]. More recently, intestinal epithelial cell GSDMD was shown to mediate goblet cell mucin secretion independent of cell death, and as such GSDMD was important in the formation of the mucus layer [ 87 ]. Therefore, GSDMD pores may serve several purposes beyond cell death and IL-1β release.…”
Section: Gsdmd Pore Function: More Than Just Cell Deathmentioning
confidence: 99%